Multi-Omics Integrative Bioinformatics Analyses Reveal Long Non-coding RNA Modulates Genomic Integrity via Competing Endogenous RNA Mechanism and Serves as Novel Biomarkers for Overall Survival in Lung Adenocarcinoma - Wang, Zhonglin; Ren, Ziyuan; Li, Rui; Ge, Junpeng; Zhang, Guoming; Xin, Yaodong; Qu, Yiqing (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNA (lncRNA) plays a crucial role in modulating genome instability, immune characteristics, and cancer progression, within which genome instability was identified as a critical regulator in tumorigenesis and tumor progression. However, the existing accounts fail to detail the regulatory role of genome instability in lung adenocarcinoma (LUAD). We explored the clinical value of genome instability-related lncRNA in LUAD with multi-omics bioinformatics analysis. We extracted the key genome instability-related and LUAD-related gene modules using WGCNA (Weighted gene co-expression network analysis) and established a competing endogenous RNA (ceRNA) network using four lncRNAs (LINC01224, LINC00346, TRPM2-AS, CASC9) and seven target mRNAs (CCNF, PKMYT1, GCH1, TK1, PSAT1, ADAM33, DDX11). We found that LINC01224 is primarily located in the cytoplasm, and LINC00346 and TRPM2-AS are primarily located in the nucleus (CASC9 unknown). We found that all the eleven genes were positively related to tumor mutational burden and involve drug resistance, cancer stemness, and tumor microenvironment infiltration. Additionally, an eight-lncRNA genome instability-related lncRNA signature was established and validated, predicting the overall survival and immunotherapy outcomes in LUAD. To conclude, we discovered that sponging microRNA, genome instability-related lncRNA functions as ceRNA, modulating genomic integrity. This research provides clinical references for LUAD immunotherapy and prognosis and interprets a potential genome instability-related ceRNA regulatory network in which LINC01224-miR-485-5p/miR-29c-3p-CCNF-RRM2 and LINC01224-miR485-5p-PKMYT1-CDK1 axes were the most promising pathways. However, the potential mechanisms underlying our findings still need biological validation through in vitro and in vivo experiments.